ANALISIS KOMPARATIF PENDAPATAN VARIETAS UNGGUL PADI DI LAHAN DEMPAM DESA SUNGAI DUA KECAMATAN RAMBUTAN - Yuwinti Nearti Yuwinti; Budi Fachrudin; Muhammad Andri Zuliansyah (Jurnal Agribisnis Indonesia, 2023)
ABSTRACT This study aims to determine the total cost, production volume, selling price and the income of lowland rice farming in Sungai Dua Village, Rambutan District, Banyuasin Regency. This research was carried out in February 2021. The determination of respondents was carried out using an experimental method, with experimental land taken on a lowland rice farm. The analysis used in this research is income analysis. The results showed that the average/ha income received by the demfarm land where for lowland rice farming using three superior varieties including the IPB 3S variety, the income was Rp. -63,701,685/Ha, Inpari 32 variety, the income is Rp. -62.493.185/Ha and Ciherang variety Rp. -61.768.185/Ha. Lowland rice farming using the comparison that the higher income is the Ciherang variety because this variety has been used by local farmers. Keywords: income, demfarm, rice varieties